Valorização dos percursos negros no Brasil: perspectivas de educação nos territórios afro-rioclarenses - Faria, Monique Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
this paper presents a reflection about the history of Brazil and Afro- Brazilian Culture, based on some experiences in Rio Claro city, SP, with the implementation of 10.639 / 03 Law, which established the compulsory teaching of African History and Afro-Brazilian Culture in the school systems of the country. In Rio Claro, the law has enabled new insights about the history and the territory of the municipality entered in educational institutions. Historical changes in the territories, cultural events, celebrations and struggles that permeate the memory and the experience of the black community in the city began to be identified. Was used as the basis for this work, the views of the individuals involved, as well as literature review about the topic and collect data locally through participatory research. Also have been verified the implementation of educational projects seeking to support the matter in question: training in African History and Afro-Brazilian Culture, started in 2012, aimed at the municipal coordinators, and the project The black community into the school, 2013, action that extended to teachers of 4th and 5th grades and Arts; These projects not only allowed the entry of a new look, but also new practices, such as conversations Griô in school space, justifying the importance of recording and dissemination of a new historical perspective of the Brazilian population, since the few official documents about territories and cultural expressions of blacks who, for the most part, remain alive in memory and orality, with those holding important part of the history of our country

este trabalho apresenta uma reflexão frente à história do Brasil e a Cultura Afro-brasileira, tendo como base algumas experiências no município de Rio Claro, SP, junto à implementação da Lei 10.639/03, que instituiu a obrigatoriedade do ensino da História da África e da Cultura Afro-Brasileira nas redes de ensino do país. Em Rio Claro, a lei abriu caminhos para que novos pontos de vista frente à história e o território do município entrassem nas instituições municipais de ensino. Passaram a ser identificadas mudanças históricas nos territórios, manifestações culturais, festas e lutas que permeiam a memória e a vivência da comunidade negra da cidade. Utilizou-se, como base para este trabalho, os pontos de vista dos sujeitos envolvidos, além de revisão bibliográfica acerca do tema e coleta de dados in loco através da pesquisa participante. Verificou-se, também, a implementação de projetos pedagógicos que buscavam dar suporte ao assunto em questão: a formação em História da África e Cultura Afro-brasileira, iniciada em 2012, destinada a coordenadores da rede municipal, e o projeto A comunidade negra vai à escola, de 2013, ação que se estendeu aos professores de 4ª e 5ª séries e Artes; esses projetos possibilitaram não só a entrada de um novo olhar, mas também de novas práticas, como conversas Griô nos espaços escolares, justificando-se pela importância do registro e divulgação de uma nova perspectiva histórica da população brasileira, visto os poucos documentos oficiais sobre os territórios e expressões culturais dos negros que, em sua maior parte, permanecem vivos na memória e na oralidade, sendo essas detentoras de parte importante da história de nosso país
Keywords: History - Study and teaching; Historia - Estudo e ensino; Cultura afro-brasileira; Ensino - Legislação; Rio Claro (SP)